PERAN HUKUM ORANG DAN KELUARGA DALAM SISTEM PERKAWINAN ADAT SUKU KOIWAI KAMPUNG NAMATOTA KABUPATEN KAIMANA - Ketaren, Dahliana (Penerbit Lafadz Jaya, 2025)
This study aims to understand the customary marriage process and the role of individual and family law in customary marriages in the Koiwai customary law community of Namatota Village, Kaimana Regency. This study emphasizes fieldwork or empirical research, first conducting legal materials and document studies. The results reveal that customary marriage in the Koiwai community is not only a bond between two individuals, but also a form of unification between two extended families or clans. This marriage has strong symbolic, social, and cultural value, manifested through a series of customary stages that have been passed down through generations. Individual and family law play a dominant role in regulating and directing customary marriage practices. Individual law determines who is eligible to marry based on clan, social status, and personal maturity. Meanwhile, family law regulates family approval, the amount of dowry, and the resolution of customary conflicts. Although religious and state law have infiltrated the Koiwai social system, customary law remains the primary basis for decision-making and the social legitimacy of marriage. Therefore, customary marriage law needs to be preserved as long as it is in accordance with societal developments and does not conflict with national marriage law.